Conflict resolution in decision making : second International Workshop, COREDEMA 2016, the Hague, the Netherlands, August 29-30, 2016, Revised selected papers /: second International Workshop, COREDEMA 2016, the Hague, the Netherlands, August 29-30, 2016, Revised selected papers. (2017) - Unknown
No abstract available